Association of lower limb compression garments during high-intensity exercise with performance and physiological responses: A systematic review and Meta-analysis - da Silva, C. A.; Helal, L.; da Silva, R. P.; Belli, K. C.; Umpierre, D.; Stein, R. (Sports Medicine, 2018)
Background: Although compression garments are used to improve sports performance, methodological approaches and the direction of evidence regarding garments for use in high-intensity exercise settings are diverse. Objectives: Our primary aim was to summarize the association between lower-limb compression garments (LLCGs) and changes in sports performance during high-intensity exercise. We also aimed to summarize evidence about the following physiological parameters related to sports performance: vertical jump height (VJ), maximal oxygen uptake (VO2max), submaximal oxygen uptake (VO2submax), blood lactate concentrations ([La]), and ratings of perceived exertion (RPE, 6-20 Borg scale). Methods: We searched electronic databases (PubMed, EMBASE, Cochrane Library, and ClinicalTrials.gov) and reference lists for previous reviews. Eligible studies included randomized controlled trials with athletes or physically active subjects (=?18 years) using any type of LLCG during high-intensity exercise. The results were described as weighted mean difference (WMD) with a 95% confidence interval (95% CI). Results: The 23 included studies showed low statistical heterogeneity for the pooled outcomes. We found that LLCGs yielded similar running performance to controls (50-400 m: WMD 0.06 s [95% CI - 1.99 to 2.11]; 800-3000 m: WMD 6.10 s [95% CI - 7.23 to 19.43]; > 5000 m: WMD 1.01 s [95% CI - 84.80 to 86.82]). Likewise, we found no evidence that LLCGs were superior in secondary outcomes (VJ: WMD 2.25 cm [95% CI - 2.51 to 7.02]; VO2max: WMD 0.24 mL.kg-1.min-1 [95% CI - 1.48 to 1.95]; VO2submax: WMD - 0.26 mL.kg-1.min-1 [95% CI - 2.66 to 2.14]; [La]: WMD 0.19 mmol/L [95% CI - 0.22 to 0.60]; RPE: WMD - 0.20 points [95% CI - 0.48 to 0.08]). Conclusions: LLCGs were not associated with improved performance in VJ, VO2max, VO2submax, [La], or RPE during high-intensity exercise. Such evidence should be taken into account when considering using LLCGs to enhance running performance. Abstract from author